ANALISIS RESEPSI KARIER DALAM IKLAN POLITIK PARTAI GERINDRA SARJANA, KERJA KERJA KERJA BAGI ALUMNI FISIP UNRI - Surti Risanti; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Advertising is a means of mass communication with their communities to like or approve an idea or object. Advertising has been spreading into the political world called political advertising. Advertising political tending to frame the issues developing in the community. As for the media of advertising political also be noted that close to the community one of which is through new media. Gerindra is party who follow a follower of most numerous in new media. One of the his political titled Sarjana, Kerja kerja kerja. This commercial illustrate that many scholars is not currently get a career appropriate. Someone certainly want to feel success in his life, one of them is success in working that marked with the progress of a career. Writing it uses type of writing qualitative descriptive focusing on reception. The author chose alumni Faculty Social and Political Science University of Riau’s alumni for college was a will in direct contact with the world of work. To it every alumni possesses the criteria a career that he wants. The object of this research is political advertising, in this community people will read a text based on the value of that they consider and understand. For that political advertising would be very interesting attention to alumni unri and compared matters relating to other issues. The determination of informant purposive use techniques of sampling and choose seven informants from any course in Faculty Social and Political Science University of Riau’s. Data obtained through a writing observation, interviews and documentation.The results of this study show that the seven informants perceive career selection in Sarjana, Kerja kerja kerja is different, and can be classified into three public positions namely dominant, negotiated and opposition. The dominant position sees that Bachelor's political adverts, career work should be formal, parents want their children to work in a formal environment. The negotiating position has a desire for a career in the company, but does not apply it in his life. In addition, parents should be able to understand the condition of their children if they do not find formal employment. Opposition position contradicts that work does not have to be a formal environment, assessing parental thinking in political advertising is not open. The differences in reception that occur are due to gender, occupation, activities and political support as well as parental support.Key word: Recepstion Analysis, Carier, Advertising Political